3D dosimetric validation of motion compensation concepts in radiotherapy using an anthropomorphic dynamic lung phantom. (29th December 2016) - Mann, P; Witte, M; Moser, T; Lang, C; Runz, A; Johnen, W; Berger, M; Biederer, J; Karger, C P
Abstract: In this study, we developed a new setup for the validation of clinical workflows in adaptive radiation therapy, which combines a dynamic ex vivo porcine lung phantom and three-dimensional (3D) polymer gel dosimetry. The phantom consists of an artificial PMMA-thorax and contains a post mortem explanted porcine lung to which arbitrary breathing patterns can be applied. A lung tumor was simulated using the PAGAT (polyacrylamide gelatin gel fabricated at atmospheric conditions) dosimetry gel, which was evaluated in three dimensions by magnetic resonance imaging (MRI). To avoid bias by reaction with oxygen and other materials, the gel was collocated inside a BAREX ™ container. For calibration purposes, the same containers with eight gel samples were irradiated with doses from 0 to 7 Gy. To test the technical feasibility of the system, a small spherical dose distribution located completely within the gel volume was planned. Dose delivery was performed under static and dynamic conditions of the phantom with and without motion compensation by beam gating. To verify clinical target definition and motion compensation concepts, the entire gel volume was homogeneously irradiated applying adequate margins in case of the static phantom and an additional internal target volume in case of dynamically operated phantom without and with gated beam delivery. MR-evaluation of the gel samples and comparison of the resulting 3D dose distribution with the planned dose distribution revealed a good agreement for the static phantom. In case of the dynamically operated phantom without motion compensation, agreement was very poor while additional application of motion compensation techniques restored the good agreement between measured and planned dose. From these experiments it was concluded that the set up with the dynamic and anthropomorphic lung phantom together with 3D-gel dosimetry provides a valuable and versatile tool for geometrical and dosimetrical validation of motion compensated treatment concepts in adaptive radiotherapy.